SOCIOCULTURAL RELATIONS AMONG PARTICIPANTS IN ARTICLES ON TEACHER AS RESEARCHER AND TEACHER AS EDUCATOR - Miranti, Ika; Mujiyanto, Januarius (Universitas Negeri Semarang, 2016)
This thesis is about sociocultural relations among participants in articles on teacher as researcher and teacher as educator. The aim of this research is explaining the sociocultural power in the opposing texts which are realized in the linguistic choices used by both authors. I choose this study because there is different role of teacher in two texts that brings out contrasting opinions about the importance of teachers becoming researchers. In this study, I used critical discourse analysis proposed by Fairclough (2001) both as research methodology and framework of the study. The findings show that sociocultural relations are realized in the lexical, grammatical and textual structures relations. From the lexical relation, both authors have different choice of words for assigning participants in the texts as well as their choices in rewording, formality, euphemism and the negative and positive evaluation. Next, from the grammatical relation, it can be seen from the tenses, the use of process types, ideological pronoun and the logical connectors. From the textual structures relation, both texts are argumentative ones and the authors use elements to persuade the readers to agree or disagree to the idea of teacher as researcher. Last, the sociocultural relation among the participants can be seen from the comparison of the types of process and participants used in both texts which show authors’ different sociocultural backgrounds that influence their standpoints. It can be concluded that linguistic choices are indeed influenced by the sociocultural backgrounds of both authors. The text on teacher as researcher was written by an Indonesian lecturer who believes that a good quality teacher is a teacher who conducts research and publishes papers in order to develop their global competence. On the other hand, the text on teacher as educator was written by an American graduate of Harvard who believes that a good quality teacher is a teacher whose first concern is on students learning, not on research. Thus, different sociocultural backgrounds of both authors resulted in the opposing ideologies and those ideologies are realized in the linguistic choices throughout the texts.